Nanostructured Particles: Stimuli‐Responsive, Shape‐Transforming Nanostructured Particles (Adv. Mater. 29/2017). Issue 29 (1st August 2017) - Lee, Junhyuk; Ku, Kang Hee; Kim, Mingoo; Shin, Jae Man; Han, Junghun; Park, Chan Ho; Yi, Gi‐Ra; Jang, Se Gyu; Kim, Bumjoon J.
Abstract : Dynamic, temperature‐driven transformation of the shape and morphology of polymer particles is demonstrated using polystyrene‐ b ‐poly(4‐vinylpyridine) block copolymers (BCPs) and temperature‐responsive poly( N ‐isopropylacrylamide) (PNIPAM) surfactants, in article number1700608 by Bumjoon J. Kim and co‐workers. The temperature‐directed positioning of PNIPAM, depending on its solubility, determines both the shape and morphology of the BCP particles, suggesting great promise of these particles for use in sensing, smart coatings, and drug delivery applications.